Quantum confinement in black phosphorus-based nanostructures. (12th June 2017) - Cupo, Andrew; Meunier, Vincent
Abstract: The modification of an idealized infinite bulk system by dimensional reduction or structural distortion results in quantum confinement effects (QCEs). For example, dimensional reduction of a black phosphorus structure leads to the realization of few-layer systems, creation of edges and surfaces, nanoribbons, quantum dots, and antidot lattices while structural distortion involves simple bending (including nanotubes) and rippling. Black phosphorus ('phosphorene' in the single-layer limit) has been of recent interest due to its relatively large charge carrier mobility and moderate semiconducting band gap, which remains direct irrespective of the number of layers. In this review the state-of-the-art properties of black phosphorus in its dimensionally reduced and structurally distorted forms are discussed, with emphasis on how quantum confinement impacts the material's properties.